Profile reconstruction and quantitative detection of planar defects with composite-mode total focusing method (CTFM). (October 2021) - Jin, S.J.; Liu, C.F.; Shi, S.Q.; Lin, L.; Luo, Z.B.
Abstract: The profile reconstruction of planar defects by ultrasonic imaging is helpful for obtaining the flaw type, size, orientation and other characteristics. In this paper, composite-mode total focusing method (CTFM) is proposed by selecting the strongest response from 21 views at every reconstructed point, realizing the profile reconstruction and quantitative detection of priori unknown planar defects except for the near-horizontal defects with a set of phased array (PA) probe and wedge. Subsequently, eight effective views corresponding to 45° longitudinal-wave wedge are determined considering Snell's law and beam directivity. The 64-element linear array probe with 5 MHz central frequency and 45° wedge were used to reconstruct a series of 5 mm length cracks with different orientations (0°, ±15°, ±30°, ±45°, ±60° and ±75°) by CTFM in simulation. The measurement errors of crack lengths, orientation angles and central depths with the 6 dB drop rule were within 0.42 mm, 1.87° and 0.58 mm, respectively. The experimental results showed that the characteristics of 5 mm length slots were presented with high accuracy, verifying the feasibility of CTFM. Meanwhile, the planar and volumetric defects can be distinguished qualitatively by CTFM. Finally, the reconstructed image by naive sum is compared with the CTFM image, and the effects of wedge angle and number of elements on profile reconstruction are discussed. Highlights: CTFM is proposed to realize the profile reconstruction and quantitative detection of priori unknown planar defects. The whole profiles of −75°–75° cracks/slots are reconstructed with high accuracy by using a set of PA probe and wedge. The detection capability of CTFM is related to the number of elements and wedge angle.